2007
DOI: 10.1017/s1049096507070667
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Textbooks for Teaching Introduction to U.S. Politics: (How) Do They See Us?

Abstract: The Committee on the Status of Lesbians, Gays, Bisexuals, and the Transgendered [LGBT] in the Profession has authorized this review of 17 recent editions of top-selling textbooks marketed for use in courses providing an introduction to U.S. politics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 2 publications
1
13
0
Order By: Relevance
“…Not only is the medium important-as attested to by the number of important studies that have specifically focused on American government textbooks (including but not limited to Allen and Wallace 2010;Carey 1982;Cigler and Neiswender 1991;Clawson and Kegler 2000;Novkov and Gossett 2007;Wallace and Allen 2008)-but visual images are a unique means of communicating information and core assumptions about contemporary society. Indeed, a number of important studies have focused solely on racial depictions in textbooks; Allen and Wallace (2010) did a broad study of pictures of African Americans in American government textbooks while 90 M. A. Eisenstein and A. K. Clark Clawson and Kegler (2000) and Clawson (2003) studied African American pictures of poverty in American government and economic textbooks, respectively.…”
mentioning
confidence: 99%
“…Not only is the medium important-as attested to by the number of important studies that have specifically focused on American government textbooks (including but not limited to Allen and Wallace 2010;Carey 1982;Cigler and Neiswender 1991;Clawson and Kegler 2000;Novkov and Gossett 2007;Wallace and Allen 2008)-but visual images are a unique means of communicating information and core assumptions about contemporary society. Indeed, a number of important studies have focused solely on racial depictions in textbooks; Allen and Wallace (2010) did a broad study of pictures of African Americans in American government textbooks while 90 M. A. Eisenstein and A. K. Clark Clawson and Kegler (2000) and Clawson (2003) studied African American pictures of poverty in American government and economic textbooks, respectively.…”
mentioning
confidence: 99%
“…First was to refer to the index to fi nd where Asian Pacifi c Americans are cited in the text. Most textbooks have an index entry called "Asian Americans" (see Novkov and Gossett ( 2007 ) in the case of gays and lesbians). A search was also made for ethnic-specifi c groups such as Japanese Americans and Chinese Americans, for well-known fi gures such as Gary Locke and Bobby Jindal, and for historical events such as the murder of Vincent Chin in 1982 and the "espionage" case of Wen Ho Lee that arose in 1999 (neither of them turned out to be mentioned in any textbook).…”
Section: Methodsmentioning
confidence: 99%
“…Modeling on Novkov and Gossett (2007), Wallace and Allen (2008) found that African Americans are the most represented of any racial/ethnic groups, but that most of the reviewed textbooks ignore the contributions of African Americans to American political development until the civil rights movement-even then, representations of this involvement are siloed in standalone sections or chapters on civil rights. Using Wallace and Allen (2008) and Novkov and Gossett (2007) as models, Monforti and McGlynn (2010) examined Latinx representation. Their findings concur with Wallace and Allen's (2008), in both the limited amount of coverage and the exiling of that coverage to civil rights chapters.…”
Section: Analyses Of Representations Of Historically Marginalized Gromentioning
confidence: 99%